KETAHANAN USANG BARANG JADI KARET PEGANGAN SETANG SEPEDA MOTOR DARI TEPUNG KULIT KERANG - Rahmaniar Rahmaniar (Jurnal Industri Hasil Perkebunan, 2016)
Padding used to strengthen and enlarge rubber volume, can improve the quality of rubbery goods’physical characteristics and vulcanization. The objectives of the research were to obtain the formulation ofrubber compound met SNI standardvaried with particle size of flour clamshell and ratio composition of padding(clamshell flour: carbon black). The experimental design of the research was Completely RandomizedFactorial Design. The first factor was concentration of clamshell flour in particle size (A): A1:30 phr, A2:40 phr, A3: 50 phr. The second was ratio composition of padding (clamshell flour: carbon black N330) (B):B1 = 15:55 phr, B2=25:45 phr and B3=35:35 phr. Testing on quality of rubber compound’s characteristicsincludevisual test, modulus, and ageing resistance including hardness, tensile strength, elongation at break.The result showed that visual test for physical compound characteristics value is no defect for all formula, 55– 104% for modulus, while compound physical test after ageing process shows 56 – 64 shore A for hardness,106 – 129 kg/cm2 for tensile strength, 336 – 579% for elongation at break. Test result for all parametersmeets SNI 06-7031-2004 as the standard for motorcycle grip handle.Keywords: rubber compound, Flour Clamshell, carbon black.